"I was Close to Helping him but Couldn't Quite get There": Psychiatrists' Experiences of a Patient's Death by Suicide. (March 2023) - Furqan, Zainab; Cooper, Rachel Beth; Lustig, Andrew; Sinyor, Mark; Nakhost, Arash; Kurdyak, Paul; Rudoler, David; Naeem, Farooq; Stergiopoulos, Vicky; Zaheer, Juveria
Objectives: A patient's death by suicide is a common experience for psychiatrists, ranging from 33% to 80%, however, research about the impact of patient suicide on psychiatrists is limited to a few survey studies. This study had three main objectives: (1) understanding the emotional and behavioural impact of a patient's suicide on psychiatrists, (2) exploring if and how the experience of a patient's suicide results in changes in psychiatrist practice patterns, and (3) understanding the tangible steps that psychiatrists and institutions take to manage the emotional and behavioural impact of patient suicide on psychiatrists. Methods: Eighteen psychiatrists were recruited using snowball sampling and interviewed to collect demographic data, followed by an in-depth exploration of their experiences of patient suicide. Interviews were then transcribed verbatim and analysed using constructivist grounded theory. Results: Study participants described strong emotional reactions in response to patient suicide. Emotional reactions were mediated by a physician, patient, relationship and institutional factors. While psychiatrists did not change the acuity or setting of their practice in response to patient suicide, they made several changes in their practice, including increased caution regarding discharges and passes from inpatient units, more thorough documentation and continuing education about suicide. Conclusions: Patient suicide has a profound impact on psychiatrists and based on the findings of this study, we propose steps that psychiatrists and institutions can take to manage the emotional, psychological and behavioural burden of this event.